Роль розчинної форми адгезійної молекули судинних клітин і дисліпідемії в розвитку атеросклерозу у хворих на гіпотиреоз - Вернигородський, В. С.; Фетісова, Н. М. (Clinical Endocrinology and Endocrine Surgery, 2012)
Study of the content of the soluble form of vascular cell adhesion molecule and lipid metabolism in 101 patients with hypothyroidism showed a significant increase in their level, especially in patients with idiopathic hypothyroidism. These data indicate that dyslipidemia and increased vascular cell adhesion molecule in the blood plasma is responsible for the formation of endothelial dysfunction and atherosclerosis in patients with hypothyroidism.